Mesenchymal Stem Cells and Metabolic Syndrome: Current Understanding and Potential Clinical Implications - Kenichi Matsushita (Stem Cells International)
Metabolic syndrome is an obesity-based, complicated clinical condition that has become a global epidemic problem with a high associated risk for cardiovascular disease and mortality. Dyslipidemia, hypertension, and diabetes or glucose dysmetabolism are the major factors constituting metabolic syndrome, and these factors are interrelated and share underlying pathophysiological mechanisms. Severe obesity predisposes individuals to metabolic syndrome, and recent data suggest that mesenchymal stem cells (MSCs) contribute significantly to adipocyte generation by increasing the number of adipocytes. Accordingly, an increasing number of studies have examined the potential roles of MSCs in managing obesity and metabolic syndrome. However, despite the growing bank of experimental and clinical data, the efficacy and the safety of MSCs in the clinical setting are still to be optimized. It is thus hoped that ongoing and future studies can elucidate the roles of MSCs in metabolic syndrome and lead to MSC-based therapeutic options for affected patients. This review discusses current understanding of the relationship between MSCs and metabolic syndrome and its potential implications for patient management.